2016
DOI: 10.3892/etm.2016.3274
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-fentanyl versus propofol-fentanyl in flexible bronchoscopy: A randomized study

Abstract: Abstract. The aim of the present study was to evaluate the effect of a combination of dexmedetomidine and fentanyl on peripheral oxygen saturation (SpO 2 ) and hemodynamic stability in patients undergoing flexible bronchoscopy. One hundred patients undergoing elective flexible bronchoscopy were randomized into either a propofol-fentanyl group (PF group; n=50) or a dexmedetomidine-fentanyl group (DF group; n=50). SpO 2 values, heart rate (HR), systolic and diastolic blood pressure (SBP and DBP), patients' cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
1
37
1
1
Order By: Relevance
“…A convenience sample size of fifty patients in each group was chosen based on the inflow of patients at our centre. Our study was similar to studies by Grendelmeier et al who investigated the safety of sedation with propofol in flexible bronchoscopy 13 in a large group and another smaller randomised study by Feng Yuan et al 14 Values presented with in ( ) as percentage %.…”
Section: Methodssupporting
confidence: 87%
“…A convenience sample size of fifty patients in each group was chosen based on the inflow of patients at our centre. Our study was similar to studies by Grendelmeier et al who investigated the safety of sedation with propofol in flexible bronchoscopy 13 in a large group and another smaller randomised study by Feng Yuan et al 14 Values presented with in ( ) as percentage %.…”
Section: Methodssupporting
confidence: 87%
“…Some studies suggest that fentanyl could cause mild respiratory depression. [13,14] However, a randomized study comparing the midazolam group and fentanyl-midazolam groups found no significant difference in blood SpO2 during bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is used in the clinic for analgesia, sedation and reduction of anesthetic agents. Reasonable application of anesthetics may reduce the occurrence of post-operative complications and rapidly exert anesthetic effects to achieve timely recovery and promote the improvement and recovery of spinal cord injury (21). Although dexmedetomidine is not recommended for pregnant females, a previous study indicated that appropriate doses of dexmedetomidine are beneficial for sedation of pregnant subjects (22).…”
Section: Discussionmentioning
confidence: 99%